Management of acetabulum fracture with contralateral neck of femur in an obese patient: a rare case report - D., Sidharth; U., Thyagarajan; B., Raghavendran; Siddharth, Raghul (International Journal of Research in Orthopaedics, 2022)
Acetabular fractures are complex fractures that pose a challenge for orthopaedic trauma surgeons due to their extension into the hip joint. The simultaneous occurrence of contralateral neck of femur fracture in an obese patient makes postoperative wound healing and rehabilitation even challenging. Here, we report a case of management of acetabulum fracture with contralateral neck of femur fracture in an obese patient. We are reporting a case of a 50-year-old obese female from Chennai who presented to the Department of Orthopaedics, SRIHER, Chennai, with complaints of bilateral hip pain and inability to weight bear on bilateral lower limb, following a high-velocity road traffic accident. She was diagnosed to have left acetabulum fracture with right hip displaced neck of femur fracture. We managed her with right hip bipolar hemiarthroplasty and left acetabulum open reduction and internal fixation. 6 month follow up showed excellent radiological and functional outcome. This case report highlights how obesity alters the surgical and medical management in obese patients with contralateral acetabulum and neck of femur fracture and the importance of a multidisciplinary approach in such polytrauma patients.